Human Resource Management Practices in Hotel Kitchen Operations: A Qualitative Study - Julia Adelina; Yuliana Yuliana; Zulfa Erianti; Indah Muthia Ayuni; Ernawati Ernawati; Rahmiati Rahmiati; Friend Zakharia; Riadi Budiman; Dhani Sudirman (Universitas Pendidikan Ganesha, 2026)
This study aims to examine HRM practices in hotel kitchen operations, focusing on workforce planning, recruitment and selection, training and development, performance appraisal, compensation, employment relations, and competency management, as well as their implications for operational effectiveness. This study adopts a qualitative research design using semi-structured interviews as the primary data collection method. The interview instrument was validated through expert judgment involving two industry practitioners and three users using the Content Validity Ratio (CVR) procedure, while reliability was ensured through inter-rater reliability testing to confirm consistency in data interpretation. Following instrument refinement, pilot interviews were conducted with six participants one manager, one head chef, and four kitchen employees to assess face validity, improve interview flow, and enhance contextual understanding. Data were analyzed using an interactive thematic analysis model encompassing data reduction, data display, and conclusion drawing. The findings indicate that HRM practices in hotel kitchens are generally implemented in a functional manner and contribute positively to employee competency development, work discipline, and operational efficiency. However, the study also identifies key challenges, including reactive workforce planning during peak periods, inconsistent performance appraisal systems, and perceived compensation inequities when workloads increase. These findings demonstrate that kitchen operational effectiveness is influenced not only by culinary technical skills but also by the integration, alignment, and fairness of HRM practices. This study contributes to the hospitality HRM literature by providing in-depth qualitative insights into back-of-house operations and highlighting the strategic role of HRM in supporting sustainable hotel kitchen performance, while offering practical implications for more systematic and equitable HRM system design.